Revised Approach to Financial Regulation and Supervision Standards Assessments in FSAP Updates. (Policy Papers; Policy Paper ;, 2009)
The Financial Sector Assessment Program (FSAP) is a central instrument for the Fund and Bank to promote financial sector soundness in member countries. The FSAP uses quantitative analysis and qualitative tools to help identify the risks and vulnerabilities of a country's financial system, ascertain the sector's developmental needs, and prioritize policy responses. Detailed assessments of the observance of relevant financial sector standards and codes, and the associated Reports on Observance of Standards and Codes (ROSCs) have been an important component of the FSAP.